1984
DOI: 10.1126/science.225.4658.195
|View full text |Cite
|
Sign up to set email alerts
|

Space Experiments with Particle Accelerators

Abstract: Electron and plasma beams and neutral gas plumes were injected into the space environment by instruments on Spacelab 1, and various diagnostic measurements including television camera observations were performed. The results yield information on vehicle charging and neutralization, beam-plasma interactions, and ionization enhancement by neutral beam injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…The S EPAC experiment on the ATLAS 1 mission was designed to accelerate electron beams up to energies of 6.25 keV with beam currents of up to 1.21 A. A previous flight of this experiment [Obayashi et al, 1984] demonstrated that the spacecraft potential must be actively controlled to achieve such high beam energy and current. This was accomplished on the ATLAS 1 mission by (1) flying the shuttle, tail-first during the artificial aurora experiments in order to collect neutralizing plasma on the conducting engine farings, (2) including three additional conducting spheres in the shuttle cargo bay, and, (3) perhaps most importantly, releasing Xe + ions during the beam pulses to neutralize the charging effects of the significant electron beam current.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…The S EPAC experiment on the ATLAS 1 mission was designed to accelerate electron beams up to energies of 6.25 keV with beam currents of up to 1.21 A. A previous flight of this experiment [Obayashi et al, 1984] demonstrated that the spacecraft potential must be actively controlled to achieve such high beam energy and current. This was accomplished on the ATLAS 1 mission by (1) flying the shuttle, tail-first during the artificial aurora experiments in order to collect neutralizing plasma on the conducting engine farings, (2) including three additional conducting spheres in the shuttle cargo bay, and, (3) perhaps most importantly, releasing Xe + ions during the beam pulses to neutralize the charging effects of the significant electron beam current.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…(SEPAC) were conducted as part of the ATLAS 1 Spacelab mission from March 24 through April 2, 1992. One of the objectives was to perform artificial aurora experiments from orbit using high-power electron beams and the optical imaging capability of the Atmospheric Emissions Photometric Imaging [Obayashi et al, 1984] showed that at these levels special means of neutralizing the Shutfie spacecraft are necessary; therefore, for ATLAS 1 the SEPAC instrument complement included three 122-cm diameter conductive spheres for charge collection and a 1.6 A hollow-cathode Xe + plasma contactor. The flight data show that the effectiveness of these charge neutralization devices was sufficient for injection of electron beams up to the highest beam currents available with the SEPAC EBA.…”
Section: The Space Experiments With Particle Acceleratorsmentioning
confidence: 99%
“…It is thus straightforward to employ electron beams injected from a space vehicle with controlled parameters to explore Artificial Aurora (AA) generated in the upper atmosphere. Such (active) AA experiments have been conducted from sounding rockets and the Spacelab (e.g., Davis et al, 1971Davis et al, , 1980Hess et al, 1971;Cambou et al, 1975Cambou et al, , 1978Cambou et al, , 1980O'Neil et al, 1978a,b;Maehlum et al, 1980a;Jacobsen, 1982;Obayashi et al, 1984;Neubert et al, 1986;Kawashima, 1988;Goerke et al, 1992;Burch et al, 1993). Besides exploring Artificial Aurora, active electron beam experiments, beginning with the Echo 1 experiment (Hendrickson et al, 1971), used injected beams as probes for studying the remote natural processes along the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited scope of this review, the setup of different experiments, as well as the electron and ion injectors and diagnostic suites onboard and on the ground, are described only schematically. The presentation is also limited to sounding rocket experiments at altitudes at and below ∼200 km to avoid the effects of return currents caused by a positive potential of beam-emitting vehicles (e.g., Linson, 1982;Obayashi et al, 1984;Managadze et al, 1988;Frank et al, 1989). The main conclusion of these experiments is that the overall dataset cannot be explained solely by collisional degradation of the beam electrons and requires collisionless beam-plasma interactions (BPI) be taken into account.…”
Section: Introductionmentioning
confidence: 99%